(3MbGFb GdJaSjQs - (3eMeO Hf GdMSjf Hf eMeO Hf ehSi GdCROj GdSdej GdfjSGHhQj, CHh YHO GdQMef,J (B412 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi NU Ggd GdMbGFb HNhGU (B,(3GfeG CNHQ ef CNHQ Yf ebOGQ s
(3BNQgG (B:s
(3hGddg Gdehab ddUhGH hGdjg GdeQLY hGdeBH hGdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi SjO GdeQSdjf s
(3GdfSNI HgG MhGTs
(3YdjgG hba GdGejQ Ydi LQjLi eTgOis
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B258s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B673s
Keywords: (3GdJaSjQ hYdhe GdbQBfs